An Analysis of Associative Meanings in Two Songs Albums of Lorde - Masriyah Masriyah; Zulfadli A. Aziz; Iskandar Abdul Samad (English Education Journal, 2019)
This research is analyzing associative meanings in Lorde’s selected songs lyric. The aimed of this study is to find out the types and the functions of associative meanings in Lorde’s selected songs lyric. This research used descriptive qualitative research approach and a major theory of associative meaning from Leech’s (1985) theory. In this research, the researcher gathered the data by collecting, marking and describing words, phrases, and sentences in the song’s lyric from two albums that contained associative meaning such as connotative meaning, social meaning, affective meaning, reflected meaning, and collocative meaning. Then, the researcher analyzed the data by classifying words, phrases, and sentences that contained types and function of associative meanings which referred to Leech’s (1985) theory, then explained the finding, and the last formulated research conclusion based on data finding and analysis. The result of this research showed that there were sixty-nine data of associative meaning as well as their functions in ten songs lyric of Lorde. There were seven data of connotative meaning, thirty-five data of social meanings, eleven data of affective meaning, eleven data of reflected meaning, and five data of collocative meanings. The dominant type of associative meaning that used in Lorde’s songs lyric is social meaning in which the lyrics used informal languages such as idioms, slangs, and colloquials.